Dual-mechanism based CTLs infiltration enhancement initiated by Nano-sapper potentiates immunotherapy against immune-excluded tumors - Yukun Huang (Nature Portfolio, 2020)
The exclusion of cytotoxic T cells remains an important barrier to the efficacy of immunotherapies. Here the authors demonstrate that the combination anti-fibrosis agents and immune-enhanced cytokines can enhance T cell infiltration in a mouse model of pancreatic cancer.